Derivation of Cumulative Residual Entropy for a Modified Skewed Distribution - Nkombou, M. B. W.; David, I. J.; Okeke, E. N. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
In this paper, the derivation of cumulative residual entropy which makes use of a probability distribution survival function for the derivation is presented. The entropy is derived for of a distribution introduced by Nkombou et al. (2025) called DUS Skew Student-t (DUSSS-t) Distribution. Specifically, the entropy derived is the Cumulative Residual Renyi Entropy (CRRE). The final result shows it is possible that other cumulative residual entropy for the DUSSS-t can be estimated following the same approach in this paper.